2021
DOI: 10.1111/plb.13294
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of the light‐harvesting chlorophyll a/b binding (Lhc) family in Gossypium hirsutum reveals the influence of GhLhcb2.3 on chlorophyll a synthesis

Abstract: Light‐harvesting chlorophyll a/b binding (Lhc) family proteins play a significant role in photosynthetic processes. Our objective was systematic identification and analysis of the Lhc family in cotton, as well as the relationship between Lhc family genes and chlorophyll synthesis during photosynthetic processes. We used genome‐wide identification, phylogenetic analysis, chromosomal distribution and collinearity to examine potential functions of Lhc superfamily genes in upland cotton. Subcellular localization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Still, no significant change was found in the content of chlorophyll b. This result is consistent with GhLhcb2.3 influence on the synthesis of chlorophyll a [ 9 ]. In contrast, AcLhcb1.5 did not affect chlorophyll content in tobacco leaves ( Figure 6 ).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Still, no significant change was found in the content of chlorophyll b. This result is consistent with GhLhcb2.3 influence on the synthesis of chlorophyll a [ 9 ]. In contrast, AcLhcb1.5 did not affect chlorophyll content in tobacco leaves ( Figure 6 ).…”
Section: Resultssupporting
confidence: 85%
“…Breeders have long been interested in the metabolism of chlorophylls because of their crucial role in plant growth and development and human health [ 2 , 42 ]. Similar to previous findings [ 9 , 43 ], the AcLhcb3.1/3.2 genes regulated chlorophyll content under biotic and abiotic stress. In tomatoes, researchers have reported that all the suffulta mutants for chlorophyll were segregated in the recessive mendelian manner in a reciprocal backcross with wild type plants [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the Lhc genes family, particularly Lhcb2 and Lhcb1, in Arabidopsis has been widely studied [131], but most of the Lhc family genes are still unknown in cotton thus far [125]. The previous research showed that cotton tetraploid species (Gossypium hirsutum and Gossypium barbadense), and their two ancestral diploid species (Gossypium raimondii and Gossypium arboreum), have been frequently used to identify the cotton genes family [24,[132][133][134].…”
Section: Role Of Ga and Sa Synthase Genes In Salt Stress Tolerancementioning
confidence: 99%